KADAR KLOROFIL DAN VITAMIN C DAUN KELOR (Moringa oleifera Lam) DARI BERBAGAI KETINGGIAN TEMPAT TUMBUH - Fajri, Fajri; Rahmatu, Rostiati; alam, nur (AGROTEKBIS, 2018)
Moringa (Moringaoleifera Lam) is one of vegetable plants high in good nutrition such as chlorophyll and vitamin C and grows in lowland and upland up to Â± 1000 m above sea level (asl). This study aimed to determine the levels of chlorophyll and vitamin C ofmoringa leaves harvested from those plants grown at different altitudes.Â Â The research was carried out at Agroindustry Laboratory of Faculty of Agriculture, TadulakoUniversity of Palu during December 2016 - February 2017. Materials used were fresh moringa leaves. The research design used a Completely Randomized Design (CRD).Â The treatment wasfour different altitudes where the plant grows i.e. 0-150 m asl; Â 151-300m asl, 301-450 m asl and> 451 m asl. Each treatment consisted of 4 replicates/groups so that there were 16 experimental units. The data obtained were analyzed using the variance test (F test) and continued with TukeyâsÂ honestly significant different test (HSD). The results showed that the altitude had a very significant effect on the contents of chlorophyll, vitamin C, and fiber, but had no significant effect on moisture content and dry weight of fresh moringa.Â Keywords: Chlorophyll, Moringa, The Height Of The Place Grows, Vitamin C